Hygienic and sensory quality factors affecting the shelf-life of Fruhe (Casu axedu) traditional Sardinian fresh cheese - Carlo Spanu; Christian Scarano; Massimiliano Venusti; Daniela Sardo; Salvatore Serra; Michela Ibba; Fabio Frau; Enrico P.L. De Santis (Italian Journal of Food Safety, 2013)
A study was conducted to evaluate the dura- bility of the traditional fresh soft cheese Fruhe manufactured in Sardinia either from goats’ or sheep’s milk. Four farmstead cheese-making plants were visited three times during the Fruhe cheese-making season. During each visit environmental samples were collected from food contact and non-food contact sur- faces in order to evaluate the presence of Enterobacteriaceae, Escherichia coli, Pseudomonas spp. and Listeria spp. In a total of 60 environmental samples, Escherichia coli and Listeria spp. were never detected, while contamination with Enterobacteriaceae and Pseudomonas spp. was observed respectively in 48% and 43% of samples. The microbiological profile of 48 Fruhe cheese samples was assessed at different time points during the product shelf-life. Aerobic mesophilic bacteria, Enterobacteriaceae, E. coli, Pseudomonas spp., Bacillus cereus and Listeria monocytogenes were investigated at 0, 7, 14 and 21 days after production. E. coli, L. monocytogenes and B. cereus were never detected in the product. Enterobacteriaceae contamination was observed, showing decreasing levels over time. Pseudomonas spp. was recovered in only two Fruhe samples (3.3%) at day 0. Sensory analysis was also conducted using a triangle test to determine whether a difference between Fruhe samples at 14 and 21 days of shelf-life exists. Based on the evolution of the microbiological profile and the sensory attributes observed in the present study, it is reasonable to assume that the product shelf-life can be feasibly extended up to 21 days.